Jelly Bean summer - Magnin, Joyce (Sourcebooks Jabberwocky, 2017)
In 1968 Pennsylvania, eleven-year-old Joyce spends the summer in a tent on the roof while she and new friend Brian bond over losing their brothers in Vietnam.